BIOLOGICAL OBSERVATIONS ON SOME HERBIVOROUS INSECTS - Seda Emel Tek; Zühal Okyar (Trakya University Journal of Natural Sciences, 2017)
Some biological characteristics of the herbivorous Archips rosana (Linnaeus) (Lepidoptera: Tortricidae), Melitaea didyma (Esper) (Lep.: Nymphalidae), Melitaea cinxia (Linnaeus) (Lep.: Nymphalidae), Allophyes oxyacanthae (Linnaeus) (Lep.: Noctuidae), Aporia crataegi (Linnaeus) (Lep.: Pieridae), Periclistus brandtii (Ratzeburg) (Hymenoptera: Cynipidae), Lymantria dispar (Linnaeus) (Lep.: Erebidae) and Mustha spinosula (Lefèbvre) (Hemiptera: Pentatomidae) obtained from Thrace Region during field studies in the period of 2013-2016 were monitored in laboratory conditions and the observations were evaluated. The carnivorous behaviour of A. rosana and M. didyma larvae, egg production by adult females of A. oxyacanthae through parthenogenesis, the defense/predatory behaviour of M. spinosula adults on L. dispar larvae and the association of P. brandtii with Pyrus communis (Linnaeus) plant are the observations reported for the first time. Furthermore, from Melitaea cinxia larva, the parasitoid Erycia festinans (Meigen) (Diptera: Tachinidae) emerged. E. festinans is a new record for Diptera fauna of Turkey. Correspondingly, M. cinxia and E. festinans is a new host-parasitoid association for Turkey.